Amperometric Gas Detection Using Room Temperature Ionic Liquid Solvents - Rogers, E; O'Mahony, A; Aldous, L; Compton, R (2010)
The electrochemistry of various gases, including oxygen, carbon dioxide, hydrogen, ammonia, hydrogen sulfide, sulfur dioxide and nitrogen dioxide, in room temperature ionic liquids (RTILs) is reviewed. The application of RTILs to gas sensor design and development is highlighted. ©The Electrochemical Society.